1973
DOI: 10.1530/acta.0.0720417
|View full text |Cite
|
Sign up to set email alerts
|

The Release in Vitro of Vasopressin Unaccompanied by the Axoplasmic Enzymes: Lactic Acid Dehydrogenase and Adenylate Kinase

Abstract: Lactic acid dehydrogenase (LDH) and adenylate kinase were shown by differential centrifugation to be mainly associated with the supernatant fraction of ox neurohypophyses. In vitro release of vasopressor activity, LDH and adenylate kinase from groups of rat neural hemilobes or slices of ox neurohypophyses was studied at rest and after stimulation with a high potassium concentration or after electrical stimulation. Although release of vasopressor activity increased considerably on stimulation, no significant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, treatment of isolated neurohypophyses with ionophores, which increase intracellular, free Ca 2+ concentration by increasing transmembrane transport, can induce secretion [5,6]. Both ultrastructural [7] and biochemical [8,9] studies suggest that secretion in the neurohypophysis as in various other endocrine systems [10], occurs by exocytosis. However, the events that are triggered by 46 Ca 2+ leading to exocytosis are not resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Also, treatment of isolated neurohypophyses with ionophores, which increase intracellular, free Ca 2+ concentration by increasing transmembrane transport, can induce secretion [5,6]. Both ultrastructural [7] and biochemical [8,9] studies suggest that secretion in the neurohypophysis as in various other endocrine systems [10], occurs by exocytosis. However, the events that are triggered by 46 Ca 2+ leading to exocytosis are not resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Some essential facts are known about the mechanism by which the neurohypophysial hormones Vasopressin and Oxytocin are released. It has been reported that on Stimulation of isolated rat neurohypophyses, vesicles containing Oxytocin and the binding protein (neurophysin) release their contents to the medium in a roughly stoichiometric way 4 , whereas axoplasma enzyme markers are not released 5 . These facts support the hypothesis that release occurs by exocytosis.…”
Section: Stimulation-dependent Uptake Of An Extracellular Marker To Smentioning
confidence: 99%